Estimation of genetic, phenotypic and environmental trends for production and reproduction traits in a flock of Corriedale sheep - BABA, M A; GANAI, T A S; RATHER, M A; HAMADANI, A; SHANAZ, S; ALAM, SAFEER; KHAN, NUSRAT N (The Indian Journal of Animal Sciences, 2020)
The aim of the present study was to estimate genetic, phenotypic and environmental trends for birth weight (BW), weaning weight (WW), six months body weight (W6), yearling body weight (W12) and age at first lambing (AFL). The genetic trends (gm), respectively, for BW, WW, W6 and W12 were 8, 44.22, 8.05 and 29.45 whereas for AFL it was –0.03 (day/year). The phenotypic trends (gm), respectively for BW, WW, W6 and W12 were –1.3, 36.06, –30.77 and 32.90 whereas for AFL it was 4.39 (day/year). The environmental trends (gm / year) respectively for BW, WW, W6, W12 were –9.3, –8.2, –38.83 and 3.45 whereas for AFL it was –4.36 (day/year). Positive and statistically significant genetic trends were recorded for all studied body weight traits whereas for AFL it was nonsignificant. Phenotypic trends for all the traits under study were statistically non-significant.